Návrh stmelených směsí do vozovek - Hepner, Urban (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Bakalárska práca sa venuje sledovaniu vlyvu tvaru skúšobného telesa stmelených zmesí pri skúšaní pevnosti v prostom tlaku. Teoretická časť práce sa venuje stmeleným zmesiam hydraulickým spojivom, skuške pevnosti v prostom tlaku a rozoberá zahraničné výskumy vedené na tému pomeru pevností medzi skúšobným telesom valca a kocky. Praktická časť bakalárskej práce opisuje prípravu zmesy pre výrobu skúšobných telies, laboratórne skúšky vedené na pripravenej zmesy, výrobu skúšobných telies a následnému testovaniu pripravených telies pevnosti v tlaku. Na záver sú výsledky zo skúšok pevnosti v prostom tlaku vyhodnocované a porovnané s výskumami v zahraničí.

The bachelor thesis focuses on the monitoring of the impact of the shape on the tested bound mixture solid during the strength tests in an uniaxial stress. The theoretical part is devoted to the hydraulic binders bound mixtures, strength test in the uniaxial stress and furthemore discusses the foreign research concerning the topic of the strength ratio between a cylinder solid and a cubical solid. Practical part of the thesis describes the act of preparation of a mixture for the production of the test solids, laboratory tests provided on the prepared mixture, the production of the test solids and finally the following tests of the prepared solids strength in the uniaxial stress. All the results from the tests of the strenght in the uniaxial stress are in the end evaluated and compared to the foreign research.
Design of the bound mixtures to pavements
Keywords: Stmelené zmesy hydraulickým pojivom; válcová a kocková pevnosť; pevnosť v prostom tlaku; Proctor modifikovaný; sitový rozbor.; Hydraulically bound mixtures; cube and cylinder compressive strength; strength in pure compression; Proctor modified; sieve analysis.